Las posibilidades de las tecnologías multimedios en la educación matemática de Costa Rica (ING) - Alfaro, Cristian (2003)
Multimedia is a new concept but with important social implications. In education it has augmented traditional teaching techniques and changed the role of the teacher. This article provides a general view of this while elucidating the meaning of the world “multimedia” and showing its potential. There is a controversy concerning the use of multimedia in the classroom. Nevertheless, our idea is not to generate further disputes but rather to show alternatives in the use of new media that favor the process of learning.